Correlation of Weather Parameters with Growth, Yield Attributes and Pod Yield of Groundnut (Arachis hypogaea L.) during Different Phenophases under Irrigated Condition of Western Rajasthan - Meena, R P; Singh, S P; Beniwal, R K (Annals of Arid Zone, 2016)
The experiment was’ conducted during 1998 and 1999 on loamy sand soil at Agricultural Research Station, Beechwal, Bikaner, to study the correlation of weather parameters with growth, yield attributes and pod yield of groundnut (Arachis hypogaea L.) during different phenophases under irrigated condition of western Rajasthan. Pod and dry matter yields of groundnut sown on 15th March and 15t April was higher compared to late sowings under irrigated condition of western Rajasthan. Dry matter accumulation correlated positively with mean temperature, leaf area index with diurnal temperature variation during sowing to flower initiation, whereas during flower initiation to physiological maturity most of weather parameters correlated positively with dry matter accumulation, crop growth rate and leaf area index. Number of pods/plant, test weight and pod yield was positively correlated with diurnal temperature variation during sowing to flower initiation, but during flower initiation to physiological maturity phenophase most of weather parameters namely maximum temperature, diurnal temperature variation, bright sunshine hours, evaporation rate, growing degree days, photothermal units and heat-use efficiency were significantly and positively correlated.